(untitled) (Ciudades, 2017)
This article addresses the actions and instruments that constitute the urban regeneration policy developed by the Spanish Central Government over the last decade, focusing on their participative dimension. The methodology and assumptions of these tools reveal an intention to devolve to local communities and stakeholders an active role in urban regeneration processes. The analysis of their participative approach has been undertaken from the perspective of Collaborative Planning. The work highlights an interest of the Central Administration to provide mechanisms and guidelines for regional and local governments so that they can set up processes of participation in the context of regeneration of their urban neighbourhoods. The trend detected reveals relevant progress and limitations, the latter namely related to the political culture and other aspects inherent to the country reality.